Identify perceived strategies for promoting happiness among nurses: Protocol for a mixed-methods study - Seyedeh Somayeh Kazemi; Mansour Ranjbar; Mohammad Rafighi (PLoS ONE, 2026)
Background Enjoyment at work and overall happiness are essential elements of a thriving workforce, particularly in high-pressure environments like healthcare. Nurses frequently experience occupational burnout and stress due to the demanding nature of their profession, which can adversely affect their performance, job satisfaction, and overall well-being. Understanding the factors that contribute to happiness in nursing is crucial, as fostering a positive work environment can lead to improved patient care, reduced turnover rates, and enhanced mental health among healthcare professionals. Objective This study aims to systematically investigate the current state of happiness among nurses in order to identify perceived strategies for enhancing their well-being. By employing a mixed-methods approach, we will gather quantitative data on happiness levels and qualitative insights into the experiences and perceptions of nurses regarding their work environment. The ultimate goal is to develop evidence-based recommendations that can be implemented within healthcare settings to promote happiness and mitigate the effects of burnout and stress, thereby contributing to a healthier and more productive workforce. Methods Utilizing a mixed-method protocol, the research consists of two distinct phases. The quantitative phase employs a two-stage sampling method to select participants from ten randomly chosen hospitals within a province, ensuring a representative sample. In the qualitative phase, snowball sampling will be utilized to achieve data saturation, allowing for a comprehensive understanding of the factors influencing happiness in nursing. Data collection will involve a range of instruments, including a demographic characteristics and occupational features checklist, the Oxford Happiness Questionnaire, and semi-structured interviews to gather in-depth insights. Data analysis will be conducted using SPSS-24 statistical software for quantitative data and MAXQDA for qualitative data, enabling a robust examination of the findings. Result The study is expected to yield a comprehensive understanding of the levels and determinants of happiness among nurses. Quantitative data will provide statistical insights into the prevalence of happiness and its correlation with demographic and occupational factors. Qualitative findings are anticipated to uncover nuanced perspectives on the challenges and enablers of workplace happiness, offering valuable context to the quantitative results. Together, these findings will inform actionable recommendations for fostering a supportive work environment in healthcare settings. Conclusions The anticipated outcomes of this study highlight the positive impact of workplace happiness on nurses’ health, job satisfaction, and overall quality of patient care. By identifying actionable perceived strategies to promote happiness in the workplace, this research aims to contribute to the development of supportive environments that enhance both staff well-being and patient outcomes. Ultimately, this study represents a vital step toward fostering a healthier, more engaged nursing workforce. Ethics approval IR.MAZUMS.IMAMHOSPITAL.REC.1402.119